FROM BURDEN TO RESILIENCE: A COMMUNITY APPROACH TO STRESS MANAGEMENT FOR FARMERS IN KARANGPRING VILLAGE: DARI BEBAN MENUJU KETANGGUHAN: PENDEKATAN KOMUNITAS UNTUK MANAJEMEN STRES BAGI PETANI DI DESA KARANGPRING - Wahyu Dini Candra Susila; Nurwahidah Nurwahidah; Erti Ikhtiarini Dewi (Faculty of Vocational Studies, Universitas Airlangga, 2026)
Background: Farmers experience high levels of stress due to heavy physical workloads and economic uncertainty. In Karangpring Village, this problem is exacerbated by limited access to mental health information, dependence on intermediaries, and the risk of crop failure due to weather-induced chronic anxiety, making stress management education urgent. Objective: To increase mental health knowledge and stress management skills among farmer groups. Method: Using a participatory educational approach through lectures, discussions, and live simulations. This activity was conducted with 22 farmers in Karangpring Village, with stages starting with a pre-test, presentation of materials, demonstration of self-relaxation techniques, and ending with a post-test. Results: The activity demonstrated a significant increase in quantitative capacity, with the average score of farmers' stress management knowledge and skills increasing by 35.7% (from a pre-test score of 5.25 to 7.125 in the post-test). Participants were able to demonstrate the stress management techniques taught to reduce mental fatigue. This increase in knowledge was positively correlated with optimizing psychological well-being to maintain farmer work productivity. Conclusion: This community service activity successfully provided a foundation for agrarian communities to manage their psychological stress independently to improve their quality of life.